1987
DOI: 10.1021/jm00391a025
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of bleomycin-mediated degradation of DNA

Abstract: Three simple and independent tests have been introduced for studying the effect of DNA intercalating compounds on the bleomycin-mediated digestion of DNA in vitro. These methods are based on hyperchromic changes of DNA solution, changes in viscosity of DNA solution, and HPLC quantitative analysis of the four bases released from digested DNA. All three tests give comparable results. However, the viscometric method is technically the simplest and at the same time the most sensitive. The amplification of the bleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…BzP, which also has two unfused rings, was weakly active in yeast but not in the V79 assay. Diverse lines of evidence support the interpretation that BLM enhancement by these compounds can be ascribed to intercalation: results from a structure-based computational DNA docking model Snyder et al, , 2006 Table X); ethidium displacement assays [Snyder, 1998]; enhanced cleavage of DNA in vitro by intercalators [Strekowski et al, 1987[Strekowski et al, , 1988[Strekowski et al, , 1991; and the finding that enhancement by DPH (Table VIII), tamoxifen (Table IX), or various acridines [Hoffmann et al, 2009] in yeast grown in the presence of intercalating agents occurs for BLM treatments in buffer in the absence of free intercalating agent.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…BzP, which also has two unfused rings, was weakly active in yeast but not in the V79 assay. Diverse lines of evidence support the interpretation that BLM enhancement by these compounds can be ascribed to intercalation: results from a structure-based computational DNA docking model Snyder et al, , 2006 Table X); ethidium displacement assays [Snyder, 1998]; enhanced cleavage of DNA in vitro by intercalators [Strekowski et al, 1987[Strekowski et al, , 1988[Strekowski et al, , 1991; and the finding that enhancement by DPH (Table VIII), tamoxifen (Table IX), or various acridines [Hoffmann et al, 2009] in yeast grown in the presence of intercalating agents occurs for BLM treatments in buffer in the absence of free intercalating agent.…”
Section: Discussionmentioning
confidence: 92%
“…Studies with isolated DNA had shown that various agents besides classical intercalators with fused heterocyclic rings bind to DNA in a manner consistent with intercalation and enhance the in-vitro degradation of DNA by BLM [Strekowski et al, 1987[Strekowski et al, , 1988[Strekowski et al, , 1991. Such unconventional intercalators with unfused rings might not be predicted to intercalate into DNA on the basis of visual inspection of chemical structure, but they were found to be active in the BLM amplification assay in Chinese hamster cells [Snyder, 1998[Snyder, , 2007Snyder and Arnone, 2002;Snyder and Brown, 2002;Snyder and Strekowski, 1999;Snyder et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Seeking to identify drugs that would enhance the antitumor activity of the DNA groove-binding drug bleomycin, they discovered that DNA intercalators could alter the topology of a naked DNA molecule in such a way as to enhance the DNA double-strand nicking activity of bleomycin [Strekowski et al, 1987[Strekowski et al, , 1991Wilson et al, 1988Wilson et al, , 1990Strekowski, 1992]. A variety of other mechanisms that could account for bleomycin amplification aside from DNA intercalation were also discussed in these studies.…”
Section: Noncovalent Dna Interactionmentioning
confidence: 99%
“…The reaction of the active BLM complex with deoxyribose portions The in vitro system consisting of DNA, BLM, molecular oxygen, ferrous ion, and DTT (the iron reducing agent) has been generally accepted as an excellent model that mimics closely the conditions in vivo for the BLM-mediated digestion of DNA. This system is being used extensively in studying BLM chemistry [2][3][4]. As part of a detailed series of studies on BLM-induced degradation of DNA under the general conditions given above [3,4], we report here that DNA is digested in a biphasic process.…”
Section: Introductionmentioning
confidence: 99%
“…This system is being used extensively in studying BLM chemistry [2][3][4]. As part of a detailed series of studies on BLM-induced degradation of DNA under the general conditions given above [3,4], we report here that DNA is digested in a biphasic process. Another objective of this paper is to develop a mechanism for explaining the puzzling biphasic effect of BLM on DNA.…”
Section: Introductionmentioning
confidence: 99%